Somatic Embryogenesis from Mature Embryos of Olea europaea L. cv. 'Galega Vulgar' and Long-Term Management of Calli Morphogenic Capacity. - Pires, Rita (2020)
Several olive cultivars, characterized by high-quality olive oil show agronomical issues such as excessive vigor, high susceptibility to biotic and abiotic stresses, and low propagation ability. They are strong candidates for breeding based on new technologies to improve their performance in a short period of time. For this reason, the first step is developing efficient somatic embryogenesis (SE) protocols. Somatic embryogenesis in olive is highly genotype-dependent for both adult tissues and mature embryos as initial explants, requiring the development of specific protocols for each genotype. Trials using cotyledons and radicles as initial explants, isolated from ripe seeds from the Portuguese olive cv. ‘Galega vulgar’, gave more than 95% calli development. Radicles proved to be the most responsive tissue for SE induction, with an average of 2 embryos per callus after callus transfer to expression medium, and 14 embryos per callus after subculture on the olive cyclic embryogenesis medium (ECO). Embryogenic competence could be recovered after several subcultures on ECO medium that maintained cyclic embryogenesis for an indeterminate period of time. Embryo conversion and plant acclimatization were also attained with high success rates. Media management for cyclic embryogenesis maintenance is of general importance for SE protocols in any olive genotype. Somatic embryogenesis was thus attained for the first time in embryo-derived explants of cv. ‘Galega vulgar’.